Manslaughter by Omission: from Criterion to Instance - Ahmad Hajidehabadi; Ali Asgari Morovat (Faṣlnāmah-i Pizhūhish-i Huqūq-i Kiyfarī, 2020)
It is possible to commission of quasi-intentional felony, the subject of three clauses of article 291, by omission with this condition that the most prominent example of felonies is to be committed by the omission in C section (falseness) of this article. In clause (a) and (b) of this article, the behavior is not effective and can consist of action and omission. The most challenging part of this research is the possibility of commission of simple mistake felony by omission. The commission of simple mistake felony, the subject of clause (a) of Article 292 is not possible by omission, since in this assumption, or the perpetrator is not responsible for the lack of the condition of ability or, in the case of liability, the crime is intentional or quasi-intentional. In clause (b) of this article, if the minor is undertaking in accordance with Article 85 of the Non-Litigious Matters Act, and a felony is committed by commission, this is simple mistake felony. Finally, although the commission of simple mistake felony, the subject of clause (c) of Article 292, is rare by omission, but it cannot be falsified.